Waterfront with Central Meat Market and early model automobiles visible on street, Ketchikan - University of Washington Libraries, Special Collections Division
Caption on image: 23672 On verso of image: Ketchikan, Alaska. Stamp on verso of image: Photograph. Canadian National Railways. Printed in Canada Visible on image, l to r: Dock No. 16[obscured]; City Dock; Ketchikan Dairy Fresh Milk, Cream & Buttermilk; Central Meat Market Wholesale and Retail Dealers in Beef, Pork, Mutton, Veal, Poultry, Butter and Eggs; H. R. Thompson & Co. General Merchandise. Filed in Alaska--Cities/Location--Ketchikan